Data characterizing a panel of biodegradable cross-linked polyester implants for sustained delivery of an anti-viral drugMendeley Data - Sungmin Jung; Jack Bufton; Zeqing Bao; Wonjoon Cho; Dean Aguiar; Christine Allen (Data in Brief)
Tenofovir alafenamide (TAF) is currently administered orally to patients for treatment of chronic hepatitis B virus infection and as a part of a combination therapy for human immunodeficiency virus (HIV) infection. A long-acting delivery system could provide several advantages as a formulation strategy for this drug including improved patient adherence, convenience, more consistent drug levels and potentially fewer side effects. To date, the vast majority of polymer-based long-acting delivery systems have been prepared from poly(lactide-co-glycolide) [1]. To expand the range of polymers available for use, cross-linkable allyl functionalized, polyester copolymers were considered for preparation of disc-shaped, implantable delivery systems for TAF. The physico-chemical properties of the implants were evaluated including thermal and spectral properties as well as in vitro stability. Subsequently the discs were loaded with TAF via a swelling-equilibrium approach and the discs were further characterized including, TAF loading and in vitro drug release. This dataset shows the potential of using these polymeric materials as a sustained delivery platform for TAF. The dataset is freely available on Mendeley Data.